PENTINGNYA PERCEIVE ORGANIZATIONAL SUPPORT DALAM MENURUNKAN PENGARUH TURNOVER INTENTIONTERHADAP WORK FAMILY KONFLIK - yunita, irma (Jurnal Ilmiah Manajemen & Bisnis, 2016)
the purpose of this research is to examine the impact of perceive organizational support to reducing the effect of work-family conflict and turn over intention. It is also examining gender and perceiver organizational support as potential moderator in that relationship. Based on data obtain from 134 supervisor of four and five star hotels in Bali, which is consist of 57 female and 77 male, we found that work-family conflict has a positive influence and significantly related to turnover intention. It is also found that perceive organizational support significantly moderated a positive relationship between work-family conflict and turnover intentions, but another moderating effect, gender have no impact on it.